Corneal lamellar grafting to repair late complications of mitomycin C trabeculectomy - Takeo Fukuchi (Dove Medical Press, 2010)
Takeo Fukuchi, Hidenobu Matsuda, Jun Ueda, Akiko Yamada, Kieko Suda, Haruki AbeDivision of Ophthalmology and Visual Science, Graduated School of Medical and Dental Sciences, Niigata University, Niigata, JapanPurpose: To report corneal lamellar grafting to repair the late-onset complications after MMC trabeculectomy.Methods: Multiple case reports.Results: A 76-year-old male with primary open-angle glaucoma (POAG) and a 55-year-old male with late developmental glaucoma complicated by bleb leaks from a microhole 10 and eight years after surgery, respectively. Severe ciliochoroidal detachment and a shallow anterior chamber were persistent in one case and bleb-related infection recurred in another. Additionally, a 46-year-old male with POAG had hypotony maculopathy with a giant ischemic bleb 18 months after surgery. Although these patients were quite resistant to medical and surgical treatments, they were successfully treated by corneal lamellar grafting without complications. Conclusions: Tectonic corneal lamellar grafting is a reliable and final surgical method to improve severe cases of hypotony maculopathy or bleb leak after mitomycin C trabeculectomy.Keywords: mitomycin C, trabeculectomy, postoperative complications, hypotony maculopathy, bleb leak, corneal lamellar grafting